2019
DOI: 10.3389/fmicb.2019.00931
|View full text |Cite
|
Sign up to set email alerts
|

Phytofabrication of Selenium Nanoparticles From Emblica officinalis Fruit Extract and Exploring Its Biopotential Applications: Antioxidant, Antimicrobial, and Biocompatibility

Abstract: In the present study, phytofabricated selenium nanoparticles (PF-SeNPs) were prepared from aqueous fruit extract of Emblica officinalis in a facile, green, economic, tactic and eco-friendly way. The aqueous fruit extract of E. officinalis was found to be rich with various secondary metabolites including phenolics (59.18 ± 2.91 mg gallic acid equivalents/g), flavonoids (38.50 ± 2.84 mg catechin equivalents/g), and tannins (44.28 ± 3.09 mg tannic acid equivalents/g) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

32
187
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 283 publications
(234 citation statements)
references
References 79 publications
32
187
2
Order By: Relevance
“…16 μg ml −1 and 24 μg ml −1 for standard drug ampicillin, respectively. Notably, in a recent study the MIC value of Emblica officinalis mediated phytofabricated nSe against E. coli was estimated to be 59.83 μg ml −1 , which is ∼3.75 fold higher compared to our reported value [32]. The MIC value for nSe and ampicillin, when tested against S. aureus, was calculated to be 32 and, 64 μg ml −1 , respectively.…”
Section: Micro Broth Dilution Assay: Minimum Inhibitory Concentrationcontrasting
confidence: 58%
See 1 more Smart Citation
“…16 μg ml −1 and 24 μg ml −1 for standard drug ampicillin, respectively. Notably, in a recent study the MIC value of Emblica officinalis mediated phytofabricated nSe against E. coli was estimated to be 59.83 μg ml −1 , which is ∼3.75 fold higher compared to our reported value [32]. The MIC value for nSe and ampicillin, when tested against S. aureus, was calculated to be 32 and, 64 μg ml −1 , respectively.…”
Section: Micro Broth Dilution Assay: Minimum Inhibitory Concentrationcontrasting
confidence: 58%
“…The antibacterial responses of nSe have been documented against major infection causing bacteria including E. coli [10,22], S. aureus [9,22,23], P. aeruginosa, and Proteus mirabilis [23]. Nanoselenium can be synthesized by different methods such as: (a) physical which include laser ablation, ultraviolet (UV) irradiation, hydrothermal [22,24,25], (b) chemical which include catalytic reduction, acid decomposition [26] and, (c) biogreen synthesis which rely on the use of certain bacteria [9,16,27,28], fungi [29] or plants species [30][31][32]. Amongst all, biogreen synthesis of nSe avoids the utilization of toxic reducing agents and post-modification steps which promotes their swift application in the food and medical industries.…”
Section: Introductionmentioning
confidence: 99%
“…In our opinion, the effect could have been influenced by the presence of multiple morphologies in the larger particles case. Other, more exotic metallic nanoparticles (Ti NPs and Se NPs) were obtained by Seydi et al [57] and Gunti et al [58], respectively, by using aqueous extracts that were obtained from different plants. In both cases, the NPs were spherical, with dimensions of 22 and 15-40 nm, respectively, and they were effective against several Gram-positive bacteria, Gram-negative bacteria, and fungal lines, with MBC/MFC values close to the positive controls (commercial antimicrobials) for Ti NPs [57].…”
Section: Au Npsmentioning
confidence: 99%
“…SeNPs have been sold on the market as a food additive in a tea product that claims to possess several health benefits [17,20]. Some studies have shown that SeNPs have unique antibacterial activities [21,22] and antifungal activities [23,24]. SeNPs can be used for food safety applications which includes as antibacterial nanocoatings [25,26], in food packaging [27,28] and in functional foods [29,30].…”
Section: Introductionmentioning
confidence: 99%